Intraoperative Physiologic Monitoring During Endovascular Revascularization for Atherosclerotic Peripheral Arterial Disease - Rockley, Mark (Université d'Ottawa / University of Ottawa, 2020)
Peripheral vascular disease (PVD) is defined by insufficient blood flow to limbs and can result in pain, gangrene, and amputation. Minimally invasive angioplasty treatments for PVD are common but suffer from high failure rates. We conducted three studies: 1) a systematic review to describe methods of intraoperative blood flow assessment; 2) a retrospective cohort study to describe the correlation between outpatient blood flow assessment and clinical outcomes; and 3) a prospective observational study to describe the reliability and association between intraoperative blood flow assessment and clinical outcomes. While limb blood flow is routinely assessed before and after interventions, intraoperative assessment has not been well described. Postoperative blood flow assessments are strongly correlated with clinical outcomes. Intraoperative blood flow assessment is feasible and strongly correlated with clinical outcomes. Intraoperative blood flow assessment may be a useful tool to guide intraoperative decision making.
Keywords: Epidemiology; Peripheral Arterial Disease; Vascular Surgery; Atherosclerosis; Physiology; Intraoperative Decision Making